Long-term outcomes following percutaneous coronary intervention for patients with rheumatoid arthritis. (25th November 2020) - Dawson, L; Dinh, D; Duffy, S.J; Brennan, A; Guymer, E; Clark, D; Oqueli, E; Freeman, M; Hiew, C; Reid, C; Ajani, A.E
Abstract: Background: Rheumatoid arthritis (RA) is the most common inflammatory arthritis and is associated with increased risk of cardiovascular events and mortality. Despite this, data regarding long-term outcomes following percutaneous coronary intervention (PCI) are limited. Methods: We identified 756 patients with RA from the Melbourne Interventional Group PCI registry (2005–2018) and compared outcomes to the remaining cohort (N=38, 579). Cox regression analysis was performed to assess risk of adverse cardiac events including long-term mortality (derived from linkage with the National Death Index [NDI]). Results: Patients with RA were older (68.9±10.0 vs. 64.6±12.0 years) and more often female (40% vs. 23%), with higher rates of hypertension (70% vs 67%), previous stroke (9% vs 6%), peripheral vascular disease (9% vs 6%), obstructive sleep apnoea (10% vs 5%), chronic lung disease (22% vs 12%), prior myocardial infarction (32% vs 27%), and impaired renal function (eGFR<60 ml/min/1.73m 2 in 31% vs 24%), while rates of current smoking were lower (20% vs. 25%), all p<0.05. Lesions were more frequently complex (ACC/AHA type B2/C in 61% vs 57%), required longer stents (>20mm in 39% vs 35%), and rates of no reflow were higher (5% vs 3%), all p<0.05. 30-day mortality was higher (4.4% vs. 3.3%, p=0.04) mainly owing to higher non-cardiac mortality (1.6% vs. 0.8%, p=0.01). National Death Index-linked long-term mortality was 28% vs. 19% (p<0.01) with mean follow-up 4.6 vs. 5.4 years. Risk of 30-day and long-term mortality (including by indication subgroup) are presented in the Table. Conclusions: Patients with RA undergoing PCI have more comorbidities and longer, more complex coronary lesions. After adjustment, risk of short-term adverse outcomes are similar, while risk of long-term mortality is higher, particularly among patients with acute coronary syndromes. Funding Acknowledgement: Type of funding source: None